2011
DOI: 10.1007/s12043-011-0194-0
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of indirectly coupled Lorenz oscillators: An experimental study

Abstract: The dynamics of indirectly coupled Lorenz circuits is investigated experimentally. The in-phase and anti-phase synchronization of indirectly coupled chaotic oscillators reported in Phys.Rev. E 81, 046216 (2010) is verified by physical experiments with electronic circuits. Two chaotic systems coupled through a common dynamic environment shows the verity of synchronization behaviours such as anti-phase synchronization, in-phase synchronization, identical synchronization, anti-synchronization, etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…A linear stability analysis has also been reported in that paper. Later, the experimental study of the same has been reported in [30]. Amplitude death in environmentally coupled chaotic systems are reported in [31,32].…”
Section: Introductionmentioning
confidence: 88%
“…A linear stability analysis has also been reported in that paper. Later, the experimental study of the same has been reported in [30]. Amplitude death in environmentally coupled chaotic systems are reported in [31,32].…”
Section: Introductionmentioning
confidence: 88%
“…The studies about the synchronization of periodic oscillators coupled through a common medium have been recently extended to chaotic systems. In this latter case, when two chaotic units are considered, both in-phase and antiphase synchronization have been numerically [13,14] and experimentally [15,16] observed. When more than two chaotic units are taken into account, phenomena such as phase synchronization, periodic collective behavior and quorum-sensing transition show up [17].…”
mentioning
confidence: 89%
“…All these type of synchronization can be achieved with various type of interactions e.g. mismatch oscillators [18], conjugate [19,20], delay [21], and nonlinear [22,23], indirect [24,25].…”
Section: Introductionmentioning
confidence: 99%